PELATIHAN FUNDAMENTAL DESAIN SISTEM APLIKASI MOBILE UNTUK PENINGKATAN LITERASI TEKNOLOGI DIGITAL SISWA SMK RAJASA SURABAYA - Titik Lusiani; Didiet Anindita Arnandy; A.B. Tjandrarini; Nunuk Wahyuningtyas; Achmad Arrosyidi (Universitas Mataram, 2026)
Digital literacy refers to the ability to understand, analyze, and design technology wisely and productively. In the context of vocational education, digital literacy is not limited to operating devices but also includes understanding mobile application system design as a solution to user needs. Vocational high school students must be equipped with fundamental system design competencies to compete in the era of digital transformation. Therefore, the mobile application system design training aimed to enhance students’ systematic and creative thinking skills. The program employed a project-based learning approach integrating theory and hands-on practice. The training was conducted through four main sessions: requirements analysis, database design, business process design, and UI/UX design. Evaluation was carried out using pre-test and post-test assessments. The results indicated a significant improvement in students’ understanding of mobile application system design. The average score increased from 77.5 in the pre-test to 91.18 in the post-test. Students were able to identify system requirements, develop simple database designs, and visualize structured business process flows. Moreover, their ability to design responsive and user-oriented interfaces improved considerably. The training proved effective in enhancing digital technology literacy, strengthening systematic thinking skills, and fostering creativity in developing mobile application solutions. In conclusion, the training not only provided practical skills but also encouraged students to continuously develop their competencies in the field of information technology.